2016
DOI: 10.1186/s12864-016-2702-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide patterns of copy number variation in the Chinese yak genome

Abstract: BackgroundCopy number variation (CNV) represents an important source of genetic divergence that can produce drastic phenotypic differences and may therefore be subject to selection during domestication and environmental adaptation. To investigate the evolutionary dynamics of CNV in the yak genome, we used a read depth approach to detect CNV based on genome resequencing data from 14 wild and 65 domestic yaks and determined CNV regions related to domestication and adaptations to high-altitude.ResultsWe identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 90 publications
4
89
0
Order By: Relevance
“…The CNVs deletion events have some advantage over duplication, due to its bi-allelic nature and compatibility with genetic analysis procedures designed for SNPs markers [9] . In this study, CNVs was used to explore the population genetic properties in some indigenous cattle breeds in Pakistan with moderate intra population frequencies as reported by Bickhart et al [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CNVs deletion events have some advantage over duplication, due to its bi-allelic nature and compatibility with genetic analysis procedures designed for SNPs markers [9] . In this study, CNVs was used to explore the population genetic properties in some indigenous cattle breeds in Pakistan with moderate intra population frequencies as reported by Bickhart et al [6] .…”
Section: Discussionmentioning
confidence: 99%
“…It is important here that selection pressure, the amount divergence between breeds (divergence time, effective population size and gene flow) can affect VST value and overall differentiation among selected populations [13,14] . At this stage a hypotheses can be developed that high VST value between populations does not necessarily involve in divergent (selection for different alleles in both populations) or can occur in the absenteeism of selection by bottlenecks or founder effects by drift [9] . All these hypotheses needs further research using large population samples size of these breeds as similar observed by Xu et al [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Zhang et al . ). However, despite the characterization of the potential selective sweep regions in the domestic yak genome, little is known about the specific effects on genome‐wide patterns of deleterious variations in yak populations that are associated with their domestication.…”
Section: Introductionmentioning
confidence: 97%
“…Although the draft genome sequence of the Yak has been available for four years, and resequencing studies have since been undertaken [6,33,34] , genetic variation in the Yakmost notably structural variation and genetic comparisons with other bovid species-Remains poorly understood. Moreover, the genome sequence of the Dzo has not been reported until now.…”
Section: Discussionmentioning
confidence: 99%